2015
DOI: 10.1039/c5ra08332j
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cu–Ag bimetallic porous nanomembrane prepared from a multi-component metallic glass

Abstract: Porous nanomembranes (PNMs) have wide applications in templates, filtration, transport and separation, water treatment, drug delivery and sensing, but the preparation of metallic PNMs has been scarcely reported due to the technical difficulty and the easy oxidization during the preparation and preservation processes. In present work, ultrathin Cu-Ag bimetallic PNMs with thicknesses of $5 to 50 nm, an area larger than 20 square micron, pore diameters of $10 to 20 nm and ligament feature sizes of $30 to 50 nm ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The surface is uniformly corroded, and no pitting is found. The nodular corrosion products are loosely packed on the surface, which is quite similar to the dealloying process . Figure d–f show the surface morphologies of the crystalline Pd‐Ni‐P alloy at different magnification.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The surface is uniformly corroded, and no pitting is found. The nodular corrosion products are loosely packed on the surface, which is quite similar to the dealloying process . Figure d–f show the surface morphologies of the crystalline Pd‐Ni‐P alloy at different magnification.…”
Section: Resultssupporting
confidence: 67%
“…The nodular corrosion products are loosely packed on the surface, which is quite similar to the dealloying process. [18] Figure 4d-f show the surface morphologies of the crystalline Pd-Ni-P alloy at different magnification. The grain size of the crystalline Pd-Ni-P alloy is in the range of 50-100 µm as shown in Figure 4e.…”
Section: Resultsmentioning
confidence: 99%
“…In ASW, the metal elements in MZC MG are more likely to lose electrons into ions in comparison with those in DW, leading to the faster formation of ZnO-like nano-plates, which could be responsible for the rapid degradation of azo dyes. As is known, the chemical activity of metal elements is different, which has been regarded as the theoretical basis of dealloying [21]. In Mg-based and Ca-based MG, Mg and Ca are dissolved first, and other inactive elements, such as Cu, Y and Ag, are remained and formed into nanoporous materials [22].…”
Section: Discussionmentioning
confidence: 99%
“…[12] Since the discovery of metallic glass, researchers have been working on improving the MG surface area, through which dealloying has proven to be an important technique. [76] In order to further improve the electrocatalytic activity and durability of these metallic glass nanowires, as well as expand its versatile applications to other energy storage fields, Doubek et al applied both the subtractive (dealloying) and additive (galvanic displacement, underpotential deposition and electrochemical deposition) surface modification techniques to these nanowires, as shown in Figure 8. Liu et al reported a Cu-Ag bimetallic porous nanomembrane through dealloying of multicomponent metallic glass.…”
Section: Electrochemical Modificationmentioning
confidence: 99%
“…Liu et al reported a Cu-Ag bimetallic porous nanomembrane through dealloying of multicomponent metallic glass. [76] In order to further improve the electrocatalytic activity and durability of these metallic glass nanowires, as well as expand its versatile applications to other energy storage fields, Doubek et al applied both the subtractive (dealloying) and additive (galvanic displacement, underpotential deposition and electrochemical deposition) surface modification techniques to these nanowires, as shown in Figure 8. [12] Subtractive dealloying from multicomponent bulk metallic glasses yields 3D nanoporous structures with increased electrochemical surface area.…”
Section: Electrochemical Modificationmentioning
confidence: 99%